L' antiquaire comme discours politique: représentations et emplois de l'État des origines chez François Hotman et Jean Papire Masson - Paolini, Lorenzo (Renaissance and reformation, 2023)
Through a discussion of the use of sources and their political implications in François Hotman's Francogallia, the author proposes to approach the question of representations of the Protestant community from the point of view of appeals to the past during the civil conflict. Technical and extra-technical material, which might seem to suggest modern critical historiography, can be understood as an ideological means of imposing a representation of national community that transcends factionalism: in this case, an ancient national community that nevertheless reflects the positions of the Protestant party. Thanks to antiquarian knowledge, the examination of the customs, languages, and institutions of the French kingdom's Gallic, Frankish, and Germanic origins becomes a political statement. Hotman's sources and their interpretation thus constitute a framework enabling him to present what we might call an ideological debate in terms of objective facts, giving at once a description of the past and a prescription for the present